Resilience for Smallholder Farmers during Pandemic: Model Conceptualization for Agriculture and Food Supply Chain Dynamics - Balkan, Büşra Atamer (Archīum Ateneo, 2021)
The COVID-19 pandemic has led to severe disruptions in the supply and demand channels of agriculture and food chains. To begin to address challenges arising from this pandemic, the “Agriculture and Food Supply Chain Resilience in the Face of a Health Crisis” project emerged as an initiative of the Agriculture Food Special Interest Group of the System Dynamics Society, and was conducted as a (virtual) group model building study with eight system dynamics researchers, practitioners, and students from six different countries. As a result of the project, a stock-flow diagram with nine modules (Food Supply Chain, Food Market, Farm Finance, Agricultural Inputs, Labor, Shelf Life, Cooperation, Information, and Community Health) was built to discuss the effects of the pandemic from the viewpoint of smallholder farmer communities. We depicted the causal relationships and feedback loops related to food supply chain resilience, mainly focusing on the barriers in input access and market access. This study has been prepared to facilitate dialogue among related stakeholders and provide critical causal loops for researchers and practitioners interested in providing formal simulation modeling solutions to mitigate the effects of these disruptions and enhancing agriculture and food supply chain resilience.